Situational-Context: A Unified View of Everything Involved at a Particular Situation - Berrocal, Javier; García-Alonso, Javier; Canal-Velasco, José Carlos; Murillo, Juan Manuel (Springer, 2016)
As the interest in the Web of Things increases, specially for the general population, the barriers to entry for the use of these technologies should decrease. Current applications can be developed to adapt their behaviour to predefined conditions and users preferences, facilitating their use. In the future,Web of Things software should be able to automatically adjust its behaviour to non-predefined preferences or context of its users. In this vision paper we define the Situational-Context as the combination of the virtual profiles of the entities (things or people) that concur at a particular place and time. The computation of the Situational-Context allow us to predict the expected system behaviour and the required interaction between devices to meet the entities’ goals, achieving a better adjustment of the system to variable contexts.
Keywords: Internet; Recursos en Internet; Páginas Web; Internet of Things; Web of Things; Context-Aware